Jawabanmu

Jawaban paling cerdas!
2014-02-09T23:25:17+07:00
1.
(fog)(x)=x^2+4x+3\\
f(g(x))=x^2+4x+3\\\\
 \frac{g(x)+6}{2.g(x)-1}=x^2+4x+3\\\\
g(x)+6=(2.g(x)-1)(x^2+4x+3)\\\\
g(x)+6=2.g(x)(x^2+4x+3)-(x^2+4x+3)\\\\
g(x)+6=(2x^2+8x+6).g(x)-(x^2+4x+3)\\\\
g(x)-(2x^2+8x+6).g(x)=-6-(x^2+4x+3)\\\\
(1-(2x^2+8x+6)).g(x)=-x^2-4x-9\\\\
(-2x^2-8x-5).g(x)=-x^2-4x-9\\\\
g(x)= \frac{ -x^2-4x-9}{(-2x^2-8x-5)}\\\\
g(x)= \frac{ x^2+4x+9}{(2x^2+8x+5)}\\\\

2.
(fog)(x)=3x-2\\
f(g(x))=3x-2\\
g^2(x)+2g(x)+1=3x-2\\
(g(x)+1)^2=3x-2\\
g(x)+1= \sqrt{3x-2}\\
g(x)= \sqrt{3x-2}-1\\
jawaban mas Oky selalu mantap dan berkelas